2012
DOI: 10.1063/1.4759019
|View full text |Cite
|
Sign up to set email alerts
|

Coherent growth of superconducting TiN thin films by plasma enhanced molecular beam epitaxy

Abstract: We have investigated the formation of titanium nitride (TiN) thin films on (001) MgO substrates by molecular beam epitaxy and radio frequency acitvated nitrogen plasma. Although cubic TiN is stabile over a wide temperature range, superconducting TiN films are exclusively obtained when the substrate temperature exceeds 710 °C. TiN films grown at 720 °C show a high residual resistivity ratio of approximately 11 and the superconducting transition temperature (Tc) is well above 5 K. Superconductivity has been conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 37 publications
4
26
1
Order By: Relevance
“…Next to the MgO peaks (on the left hand side), the respective strong TiN peaks at 42.6 • (200) and 92.7 • (400) are visible, indicating epitaxial growth. Such an epitaxy is expected and has been observed before [43,44,37,54], as both MgO and TiN have a cubic rocksalt structure, and the bulk lattice mismatch is only ∼ 0.6% [38,44]. The full range of 2Θ is shown in Fig.…”
Section: Surface Topography and Crystal Structuresupporting
confidence: 62%
“…Next to the MgO peaks (on the left hand side), the respective strong TiN peaks at 42.6 • (200) and 92.7 • (400) are visible, indicating epitaxial growth. Such an epitaxy is expected and has been observed before [43,44,37,54], as both MgO and TiN have a cubic rocksalt structure, and the bulk lattice mismatch is only ∼ 0.6% [38,44]. The full range of 2Θ is shown in Fig.…”
Section: Surface Topography and Crystal Structuresupporting
confidence: 62%
“…Therefore, it is shown that the superconducting properties of TiN films depend on the lattice constant. The observed value of a 0 with the maximum T C is close to the reported value for TiN films deposited by molecular beam epitaxy (MBE) [8]. The ρ 10 is proportional to the a 0 , except for the case of the TiN film deposited at 1073 K. The decrease in ρ 10 with decreasing nitrogen partial pressure is expected from the decrease in the number of defects due to interstitial nitrogen atoms.…”
Section: A Crystal Structure and Transport Properties Of Tin Thin Filmssupporting
confidence: 82%
“…Another advantage is the low electrical resistivity of sputter deposited TiN (16 µΩ cm) and a surface roughness below 1 nm. 8,9 The lattice constant of TiN (fcc structure) is 4.24Å and therefore suitable for various Heusler compounds. By rotating the unit cell of the Co-based Heusler compounds by 45 degree a lattice mismatch of about 5 % is achieved.…”
Section: Introductionmentioning
confidence: 99%